2018
DOI: 10.1007/s12152-018-9373-8
|View full text |Cite|
|
Sign up to set email alerts
|

Deflating the “DBS causes personality changes” bubble

Abstract: The idea that deep brain stimulation (DBS) induces changes to personality, identity, agency, authenticity, autonomy and self (PIAAAS) is so deeply entrenched within neuroethics discourses that it has become an unchallenged narrative. In this article, we critically assess evidence about putative effects of DBS on PIAAAS. We conducted a literature review of more than 1535 articles to investigate the prevalence of scientific evidence regarding these potential DBS-induced changes. While we observed an increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 76 publications
2
73
0
Order By: Relevance
“…More generally, a recent literature review found only relatively limited evidence that DBS affects identity, agency, authenticity, and related aspects of the individual. The authors conclude that additional empirical work is therefore needed to inform normative theorizing about these topics in neuroethics [29]. …”
Section: Personal Identity and Agencymentioning
confidence: 99%
“…More generally, a recent literature review found only relatively limited evidence that DBS affects identity, agency, authenticity, and related aspects of the individual. The authors conclude that additional empirical work is therefore needed to inform normative theorizing about these topics in neuroethics [29]. …”
Section: Personal Identity and Agencymentioning
confidence: 99%
“…The stimulation-dependent nature of psychiatric symptoms has been contested by Gilbert et al [23], who suggest that they may reflect a worsening of preexisting psychiatric disorders or aggravation of difficult family relationships in the setting of major surgery, less related to electrical stimulation than to premorbid psychiatric, personality and psychosocial functioning. In particular, these authors propose that debate regarding the neuroethical consequences of DBS relies largely upon speculative assumptions rather than empirical evidence.…”
mentioning
confidence: 99%
“…Control, Personality, and Neuroethical Issues in the Use of DBS for PD Gisquet (2008) have claimed that DBS is a disruptive experience for some patients due to the associated loss of control of the illness and of one's life, and the possibility of undesired personality changes incurred by the use of this technology. These concerns generated considerable conceptual neuroethical discourse, however, most publications addressing this topic were not based on empirical data (Frederic Gilbert and Ineichen, 2018). Thus, efforts are underway to employ empirical methods to re-examine assertions that DBS results in diminished control and undesired personality changes.…”
Section: The Ieee Brain Initiative Neuroethics Programmentioning
confidence: 99%